Truancy and job satisfaction among dual career couples towards organizational sponsored day care amenities in developing nation - Gautam, Omvir; Agrawal, Pooja (Serbian Journal of Management, 2020)
The prevalent concern in the present work environment is daycare amenities for dual career couples in developing nations like India. It plays a significant role in improvising the employee-employer relationship. This study identifies the pivotal factors like truancy and job satisfaction among dual career couples towards organizational sponsored daycare amenities. Moreover, role of organizational sponsored daycare amenities has been examined along with moderators like gender and numbers of children A descriptive research design was employed along with the usage of a self-administrated questionnaire to a sample of 197 employees from two states of Punjab i.e Amritsar and Punjab, India; to assess the moderator role of gender and number of children towards the organizationally sponsored daycare amenities. Organizational sponsored daycare amenities towards truancy rate and job satisfaction were found significant. Organizational sponsored daycare amenities are positively new to employees and even for employers in developing nations like India. Future studies may thrust on implications of organizational sponsored daycare amenities in the nourishment of organizational existence for longer eternity.
Keywords: gender; organizational sponsored; day care; TRUANCY; job satisfaction; child-care